Primary Paediatric Bronchial Airway Epithelial Cell in Vitro Responses to Environmental Exposures - McInnes, Neil (Int J Environ Res Public Health, 2016)
The bronchial airway epithelial cell (BAEC) is the site for initial encounters between inhaled environmental factors and the lower respiratory system. Our hypothesis was that release of pro inflammatory interleukins (IL)-6 and IL-8 from primary BAEC cultured from children will be increased after in vitro exposure to common environmental factors. Primary BAEC were obtained from children undergoing clinically indicated routine general anaesthetic procedures. Cells were exposed to three different concentrations of lipopolysaccharide (LPS) or house dust mite allergen (HDM) or particulates extracted from side stream cigarette smoke (SSCS). BAEC were obtained from 24 children (mean age 7.0 years) and exposed to stimuli. Compared with the negative control, there was an increase in IL-6 and IL-8 release after exposure to HDM (p ≤ 0.001 for both comparisons). There was reduced IL-6 after higher compared to lower SSCS exposure (p = 0.023). There was no change in BAEC release of IL-6 or IL-8 after LPS exposure. BAEC from children are able to recognise and respond in vitro with enhanced pro inflammatory mediator secretion to some inhaled exposures.